Development of canned chevon pate - Siy, Iris
ABSTRACT This study aimed to develop canned chevon pâté. A modified pâté formulation was subjected to a consumer acceptance test to determine its acceptability, The thermal process schedule for the canned chevon pâté was determined using Ball's Mathematical Method and verification of the calculated process was done. Fifty random untrained panelists recruited from the College of Home Economics student body participated in the sensory evaluation. The nine-point hedonic scale was used to determine the quality and acceptability ratings for the pâté and the mean scores and standard deviations calculated from Microsoft Excel 2007 were reported. The initial chevon pâté formulation had a very low acceptability score of 4 (dislike slightly) for the spreadability, Product improvements such as increase in water content and decrease in oil were done to improve the spreadability of the product. The reformulated chevon pâté was again subjected to a consumer acceptance test to determine its acceptability. The reformulated chevon pâté obtained a score of 5 (neither like nor dislike) for the spreadability and a score of 6 (like slightly) for the overall acceptability. The reformulated chevon pâté formulation was then used to establish the process schedule which was computed to be approximately 54 minutes using Clostridrium sporogenes as the reference organism. The calculated process was verified using ut-out test, phsico-chemical tests, microbial examination and sensory evaluation. Results showed that the calculated process was lethal enough to produce a safe and acceptable canned chevon pâté although post-process leakage was determined in one of the verification runs due to faulty can seams. Further improvements in the spreadability of the canned chevon pâté are recommended to be able to obtain a product that can be successfully marketed locally and internationally.